STRATEGI KAMPANYE “KANG PISMAN” PADA MEDIA LUAR RUANG DI WILAYAH REKREASI KOTA BANDUNG - Merryam Agustine; Rully Khairul Anwar (Journal of Tourism Destination and Attraction, 2020)
This study aims to determine the strategy carried out in the campaign of environmental care with the slogan "Kang Pisman" on outdoor media in the recreational area of ​​Bandung city, which is around Cihampelas road. The focus of this research are to find out the message strategy on the slogan "Kang Pisman",and the strategy of placing campaigns in outdoor media. This research method uses qualitative research methods with a case study approach. The method of data collection is by the method of data triangulation, where data is obtained from observations, interviews, and documentation. The object of this research is environmental awareness campaign with "Kang Pisman" slogan. The results of this study indicate that the message strategy is carried out to change knowledge, attitudes, and behaviors, the strategy of placing outdoor campaigns is intended to be easily seen and read by many people passing by, both Bandung citizen, local and international tourists, and the strategy of placing campaigns in the recreational area is to make tourists take part in environmental care activities to reduce the amount of waste when traveling to Bandung city.